GEOKIMIA AIRTANAH LERENG BAGIAN TIMUR GUNUNG CIREMAI, KABUPATEN KUNINGAN, PROVINSI JAWA BARAT - , YOGY PALAM ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Groundwater is a source of water for the quality and quantity sufficient potential to be developed to meet the basic needs of living things. Research on groundwater is closely related to the hydrogeological state consisting of three key elements, that are geology, physics and chemistry of groundwater. This research focused on the geochemistry of groundwater in the eastern slopes of Ciremai Volcano. The purpose of this research are to determine the type of groundwater by groundwater geochemistry, the relationship between morphology and lithology to the geochemistry of groundwater in the research area, and interpretation of the hydrogeological system that developed, related to the emerge of springs in the research area. The method is performed by observing the state of geological, hydrogeological plus geoelectric survey conducted in the field to determine the natural condition of the research area. This was followed by the analysis of groundwater geochemistry to get the type of groundwater, and then combined with the natural conditions of the research area, so the relationship of groundwater types based on geochemistry with the natural conditions of the research area can be known, especially in terms of geology. From these relationships can then be interpreted hydrogeological systems that exist in the research area. The analysis showed groundwater type that exist in the research area geochemically consists of 5 types, that are (a) Na++K+ - Ca2+ HCO3 -, (b) Na++K+ - Mg2+ HCO3, (c) Na++K+ - Ca2+ - Mg2+ HCO3 -, (d) Mg2+ - Na++K+ - Ca2+ HCO3 -, (e) Na++K+ Cl-. Morphology effect on the type of groundwater relation to the surface elevation. The decrease in surface elevation will increase the value of groundwater temperature, amount of dissolved salts, electrical conductivity, and the concentration of certain ions such as HCO3 -, Cl- and Na+, Ca2+, Mg2+. Lithology influent in determining the content of groundwater geochemistry, groundwater generally comes from an aquifer that is composed of laharik breccias and andesitic lava, except for the hot springs that show comes from a mixture of aquifers laharik breccias and andesitic lava with Tertiary sedimentary aquifer that affected with geothermal activity. Hydrogeological system that developed in the research area consists of two types, that are (a) Hydrogeological system I : Hydrogeological system I A (Local groundwater flow system related to recharge area in eastern slope of Ciremai Volcano )